2021
DOI: 10.3233/shti210545
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Representation of Genomic Data in HL7 FHIR and OMOP CDM

Abstract: High throughput sequencing technologies have facilitated an outburst in biological knowledge over the past decades and thus enables improvements in personalized medicine. In order to support (international) medical research with the combination of genomic and clinical patient data, a standardization and harmonization of these data sources is highly desirable. To support this increasing importance of genomic data, we have created semantic mapping from raw genomic data to both FHIR (Fast Healthcare Interoperabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Further medical specialties were environmental health (2%, 1/49) [ 64 ], genomic cancer medicine (2%, 1/49) [ 51 ], neuroimaging research (2%, 1/49) [ 12 ], and pulmonary hypertension (2%, 1/49) [ 35 ]. Despite studies implementing FHIR in specific use cases, 55% (12/22) of the studies [ 1 , 12 , 22 , 23 , 25 , 35 , 43 , 50 , 52 , 58 , 64 , 69 ] reported generic solutions conferrable to other use cases. Details on study objectives with regards to FHIR use can be found in Table 2 and Multimedia Appendix 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further medical specialties were environmental health (2%, 1/49) [ 64 ], genomic cancer medicine (2%, 1/49) [ 51 ], neuroimaging research (2%, 1/49) [ 12 ], and pulmonary hypertension (2%, 1/49) [ 35 ]. Despite studies implementing FHIR in specific use cases, 55% (12/22) of the studies [ 1 , 12 , 22 , 23 , 25 , 35 , 43 , 50 , 52 , 58 , 64 , 69 ] reported generic solutions conferrable to other use cases. Details on study objectives with regards to FHIR use can be found in Table 2 and Multimedia Appendix 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 49 studies, 37% (n=18) did not report on or use additional standards or terminologies [ 12 , 22 - 24 , 27 , 28 , 30 - 32 , 38 , 39 , 48 , 50 , 55 , 57 , 64 , 66 , 69 ]. SNOMED CT [ 1 , 25 , 26 , 35 , 37 , 43 , 45 - 47 , 51 , 55 , 56 , 65 , 70 ] and LOINC [ 25 , 26 , 35 , 37 , 42 - 45 , 47 , 49 , 51 , 55 , 56 , 58 , 61 , 65 , 68 , 70 ] were reported to be used by 29% (n=14) and 37% (n=18) of the studies, respectively; 18% (n=9) of the studies used International Classification of Diseases 10th Revision [ 25 , 26 , 35 , 37 , 49 , 51 , 58 , 65 , 68 ] and 12% (n=6) used OMOP CDM [ 26 , 29 , 35 , 47 , 52 , 60 ]; and 43% (n=21) of the studies used additional standards which were categorized under “Other” ( Table 1 ) [ 26 , 34 - …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations